2021
DOI: 10.1371/journal.pone.0250644
|View full text |Cite
|
Sign up to set email alerts
|

Assessing private provider perceptions and the acceptability of video observed treatment technology for tuberculosis treatment adherence in three cities across Viet Nam

Abstract: Background The World Health Organization recently recommended Video Observed Therapy (VOT) as one option for monitoring tuberculosis (TB) treatment adherence. There is evidence that private sector TB treatment has substandard treatment follow-up, which could be improved using VOT. However, acceptability of VOT in the private sector has not yet been evaluated. Methods We conducted a cross-sectional survey employing a theoretical framework for healthcare intervention acceptability to measure private provider p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(46 reference statements)
3
2
0
Order By: Relevance
“…Health care providers and patients perceived VDOT as a cost- and time-saving approach in the long run compared with costs that are likely to be incurred with frequent travel when using in-person DOT. Similar findings were reported in a study of health care providers in the private sector in urban Vietnam [ 39 ]. In addition, 4 studies quantified the time spent on the treatment observation process and found a significantly larger saving in time and money compared with the usual DOT [ 21 , 36 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Health care providers and patients perceived VDOT as a cost- and time-saving approach in the long run compared with costs that are likely to be incurred with frequent travel when using in-person DOT. Similar findings were reported in a study of health care providers in the private sector in urban Vietnam [ 39 ]. In addition, 4 studies quantified the time spent on the treatment observation process and found a significantly larger saving in time and money compared with the usual DOT [ 21 , 36 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…The technology usability barrier is likely to affect mostly older patients and those without formal education. Similar findings have been reported in VDOT studies conducted in Vietnam, Cambodia, and South India [ 23 , 37 , 39 ]. In our experience with the VDOT pilot study, intensive training with clear instructions to patients helped them gain the required skills.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We developed an English language acceptability survey consisting of 27 questions (S1 Survey) using a theoretical framework for healthcare intervention acceptability which encompasses seven key constructs: 1) ethicality; 2) intervention coherence; 3) burden; 4) opportunity cost; 5) perceived effectiveness; 6) self-efficacy; and 7) affective attitude (S1 Table) [26,27]. Additional questions captured pharmacist demographics and measured perceptions of the implementation plan and usability of the technology.…”
Section: Acceptability Surveymentioning
confidence: 99%